The Empowerment of Science Teachers in Developing Education Sustainable Development (ESD)-based Learning Instrument for Teachers Affiliated with Subject Teachers’ Working Group (MGMP) for Science in Surakarta City - Bramastia; Utami, Budi; Gunawan, Kadek Dwi Hendratama; Suciati; Rini, Endah Febri Setiya; Salsabila, Tiara Hasna (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
PISA 2022 data shows that Indonesian students’ critical thinking skills and scientific literacy are still low. This situation is worsened by science learning having not integrated the Education for Sustainable Development (ESD) approach. This community service program held by the UNS SESD RG aims to empower science teachers at the MGMP (Subject Teachers’ Working Group) for Science in Surakarta City in developing ESD-based learning instruments. The methods used include needs analysis, workshops, assignments, and evaluation. Problems encountered by teachers include poor awareness of ESD, limited publications of research result, and no implementation of project-based learning. Solutions provided include training, mentoring, and the use of educational technology. The results of activity indicate an increase in teacher capacity in developing contextual and innovative ESD-based learning instrument. This program also supports the achievement of SDGs, particularly in aspects of quality education and climate action.